A proposta de Will Kymlicka de uma teoria liberal dos direitos das minorias como plataforma de viabilidade do projeto sociopolítico de Alasdair Macintyre - Costa, Jardel de Carvalho (2019)
The liberal tradition, in particular, that of egalitarian liberalism recognized by the unflinching defense of human dignity always had as main objective ensure the peaceful coexistence among all sorts of cultures through principles of justice that ensure freedom and equality of oportunities for all. It is in this context that arises the scottish Alasdair MacIntyre, a radical critic of the liberal traditon. Starting from the aristotelic-thomist, MacIntyre has guided his philosophy in what he entitles rationality of traditions, which in other terms has among its main requisites, confront the positions of all sorts of traditions trying to find the best set of reasons that prove the superiority of any of those traditions at stake. Anchored in this kind of rationality, he has acused liberalism of failling as a model of sociability that ensures the good life. Thus, he has proposed that the better way of life may be found in small local communities stablished under the virtue ethics of the aristotelic-thomist branch. However, in this context also emerges the canadian philosopher Will Kymlicka intending to correct some of the shortcomings of the liberal tradition, in particular, recognize the concrete form of cultural minorities in many Multicultural States, having proposed surprisingly the right to self-govern for some communities, and also, chairs in the parliament that are exclusive to members of such communities. So, the present dissertation aims to evaluate up to what point the liberal tradition represented by Kymlicka can offer a platform of protection and maintenance of MacIntyre's socio-political project since it is urgent that we find some kind of support that ensure the survival of local communities. In this sense, we put into practice the model of rationality proposed by the scottish philosopher and test the strenght of both traditions reasoning: if there is any superiority in any of them, as well as its shortcomings; and proposing solutions that go beyond themselves. For such task, we drafted in the first chapter the contemporary landscape of the liberal-communitarian debate, stretching it to contemporary multicultalist proposals. In the second chapter we detailed in what consists MacIntyre's model of rationality, as well as his socio-political proposal. In the third chapter we explain Will Kymlicka's proposal of diferentiated citizenship Rights, as well as the problem of social stability. Concerning the fourth chapter, we tested the capacity of Kymlicka's proposal faced with the politics of virtues defended by MacIntyre trying to demonstrate some elements: first, how much Kymlicka's proposal of ensuring the right to selfgoverment to communities is relevant to the protection and maintenance of social networks grounded in virtue ethics. Secondly, what conception of moral subject is proposed by the canadian philosopher in order to keep the stability among selfgoverned communities. And at last, we point out some shortcomings of both authors and proposed as an alternate solution, the implementation of what we coin intercultural democracy.